The Relationship Between Principal Leadership and Student Achievement in Islamic Religious Education - Bossta Kaban (Yayasan Bayt Shufiya Nusantara, 2025)
Leadership is recognized as a decisive factor in determining the success of educational institutions, influencing not only administrative performance but also the quality of teaching and learning outcomes. Using a quantitative research approach, data were collected from students at Madrasah Aliyah Swasta (MAS) Nahdhatul Islam Mancang, located in Selesai Subdistrict, Langkat Regency, through structured questionnaires distributed to 100 upper-grade students. The results reveal that the principal’s leadership style has a significant effect on student achievement, particularly through dimensions such as supervision, motivation, communication, and moral exemplarity. In Islamic education, leadership extends beyond managerial functions to encompass moral and spiritual responsibilities, reflecting values of uswah hasanah, syura, and amanah. The findings emphasize that effective leadership not only enhances academic success but also strengthens the moral and spiritual formation of students, thereby supporting the holistic goals of Islamic education.